\(^2\)+ 3\(^3\)+ 3\(^4\)+ .....">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 10 2020

Trả lời :

Đặt A = 1 + 32 + 33 + 34 + ... + 32008

=> 3A = 3 + 33 + 34 + 35 + ... + 32009

=> 3A - A = (3 + 33 + 34 + 35 + ... + 32009) - (1 + 32 + 33 + 34 + ... + 32008)

=> 2A = 32009 - 1

=> A = \(\frac{3^{2009}-1}{2}\)

25 tháng 2 2020

Ta có : A=1+32+34+...+32008

\(\Rightarrow\)9A=32+34+36+...+32010

\(\Rightarrow\)9A-A=(32+34+36+...+32010)-(1+32+34+...+32008)

8A=32010-1

\(\Rightarrow\)8A-32010=32010-1-32010=1

Vậy 8A-32010=1

Học tốt!

#Huyền#

21 tháng 7 2018

a, \(\dfrac{-7}{9}.2\dfrac{3}{4}\)

= \(\dfrac{-7}{9}.\dfrac{11}{4}\)

= \(\dfrac{-77}{36}\)

b, \(\dfrac{2}{3}+\dfrac{1}{3}.\dfrac{-2}{5}\)

= \(\dfrac{2}{3}+\dfrac{-2}{15}\)

= \(\dfrac{10}{15}+\dfrac{-2}{15}\)

= \(\dfrac{-8}{15}\)

c , \(\dfrac{2}{3}-4\left(\dfrac{1}{2}+\dfrac{3}{4}\right)\)

= \(\dfrac{2}{3}-4.\dfrac{5}{4}\)

= \(\dfrac{2}{3}-5\)

= \(\dfrac{-13}{3}\)

d, \(\left(\dfrac{1}{-3}+\dfrac{5}{6}\right).11-7\)

= \(\dfrac{1}{2}\) . 11 - 7

= \(\dfrac{11}{2}-\dfrac{14}{2}\)

= \(\dfrac{-3}{2}\)

e, \(\dfrac{3}{4}.15\dfrac{1}{3}-\dfrac{3}{4}.43\dfrac{1}{3}\)

= \(\dfrac{3}{4}.\left(15\dfrac{1}{3}-43\dfrac{1}{3}\right)\)

= \(\dfrac{3}{4}.-28\)

= \(-21\)

24 tháng 4 2017

1.\(\frac{5}{7}.\frac{5}{11}+\frac{5}{7}.\frac{2}{11}-\frac{5}{7}.\frac{14}{11}\)

\(=\frac{5}{7}.\left(\frac{5}{11}+\frac{2}{11}-\frac{14}{11}\right)\)

\(=\frac{5}{7}.\frac{-7}{11}=\frac{5.\left(-7\right)}{7.11}=\frac{5.\left(-1\right)}{1.11}=\frac{-5}{11}\)

\(C=\frac{-3}{7}.\frac{5}{9}+\frac{4}{9}.\frac{-3}{7}+2\frac{3}{7}\)

\(=\frac{-3}{7}.\left(\frac{5}{9}+\frac{4}{9}\right)+2\frac{3}{7}\)

\(=\frac{-3}{7}.1+2\frac{3}{7}=\frac{-3}{7}+2\frac{3}{7}=2\)

24 tháng 4 2017

câu 1:

\(\frac{5}{7}.\left(\frac{5}{11}+\frac{2}{11}-\frac{14}{11}\right)=\frac{5}{7}.-\frac{7}{11}=\frac{-5}{11}\)

25 tháng 8 2018

Bài 1

a)\(\left(-\dfrac{2}{3}\right).\dfrac{3}{11}-\left(\dfrac{4}{3}\right)^2.\dfrac{3}{11}\)

\(=\dfrac{3}{11}.\left[\left(-\dfrac{2}{3}\right)-\left(\dfrac{4}{3}\right)^2\right]\)

\(=\dfrac{3}{11}.\left[\left(-\dfrac{2}{3}\right)-\dfrac{4}{3}.\dfrac{4}{3}\right]\)

\(=\dfrac{3}{11}.\left[\left(-2\right).\dfrac{4}{3}\right]\)

\(=\dfrac{3}{11}.\left(-\dfrac{8}{3}\right)\)

\(=-\dfrac{24}{33}\)